Praktik Benchmarking dalam Peningkatan Mutu dan Daya Saing Lembaga Pendidikan: Kajian Sistematis Literatur - Ahmad Syadidunni’am; Andini Ramadiniyah; Umi Nur Khamidah; Mu’alimin Mu’alimin (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
The rapid advancement of digital technology, the increasing demand for educational quality, and the adoption of sustainability principles have significantly reshaped institutional management in modern education systems. Within this context, benchmarking and digital innovation emerge as crucial strategies to enhance governance effectiveness, strengthen institutional competitiveness, and foster sustainable educational transformation. This study systematically reviews recent research published between 2023 and 2025 to identify emerging trends in educational innovation, institutional governance, and sustainability strategies. Using a systematic literature review approach, relevant articles were retrieved from Google Scholar and Publish or Perish with keywords such Educational Benchmarking, Quality Management, Institutional Innovation, Adaptive Learning, Digital Transformation. Out of 35 articles identified, seven were selected for in-depth analysis based on thematic relevance and validity. The findings highlight five dominant themes: fundamental concepts of benchmarking in education, benchmarking as a strategy for quality improvement, benchmarking and institutional competitiveness, implementation challenges, and practical implications with future research directions. The synthesis suggests that the effectiveness of benchmarking depends on the synergy between leadership transformation, knowledge management, and digital benchmarking systems. This study concludes by recommending further exploration of benchmarking integration with green education and data-driven governance as a strategic pathway to advance sustainable education in the future.